2016
DOI: 10.1080/2162402x.2016.1160184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of innate and adaptive immunity contributing to the antitumor effects of PD1 blockade in an orthotopic murine model of pancreatic cancer

Abstract: Despite the clinical success of anti-PD1 antibody (α-PD1) therapy, the immune mechanisms contributing to the antineoplastic response remain unclear. Here, we describe novel aspects of the immune response involved in α-PD1-induced antitumor effects using an orthotopic Kras (G12D)/p53(R172H)/Pdx1-Cre (KPC) model of pancreatic ductal adenocarcinoma (PDA). We found that positive therapeutic outcome involved both the innate and adaptive arms of the immune system. Adoptive transfer of total splenocytes after short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Salazar and colleagues demonstrated considerable ICI response in immunocompetent PDAC mice and, thus it is plausible that optimal cytotoxic effects from ICIs in clinical regimens may require both direct PDAC targeting combined with robust immune cell responses. 41…”
Section: Discussionmentioning
confidence: 99%
“…Salazar and colleagues demonstrated considerable ICI response in immunocompetent PDAC mice and, thus it is plausible that optimal cytotoxic effects from ICIs in clinical regimens may require both direct PDAC targeting combined with robust immune cell responses. 41…”
Section: Discussionmentioning
confidence: 99%
“…Tumor volumes were measured thrice weekly using manual calipers. Lower doses from previously published regimens of anti-PD-1 [ 34 , 42 ] and anti-CTLA-4 [ 43 , 44 ] were chosen to more readily observe potential synergy with shIDO-ST.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a novel subset of anti-tumor neutrophils have been identified in the early stages of NSCLC that are capable of inducing anti-tumor immunity through attainment of antigen presentation capabilities [ 30 , 31 , 32 , 33 ]. Our recent studies in pancreatic ductal adenocarcinoma (PDAC) have also shown that depletion of neutrophils and monocytes abrogate the anti-tumor effects of anti-PD-1 treatment, demonstrating the importance of tumor-associated myeloid cells in checkpoint blockade efficacy [ 34 ]. Increasing antigen stimulation of T cells through increased presentation by APCs and/or converted MDSC may sensitize permanently dysfunctional T cells to ICB therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 71 In pancreatic cancer, infiltrating Treg in tumor microenvironment upregulated CTLA-4 (cytotoxic T-lymphocyte antigen 4) and PD-1, thus, blockage of these pathways enhance anti-tumor immunity. 72 TAMs with CD120a, CD120b secret NO, resulting in promoting the apoptosis of activated T cells in tumor tissue. 73 In pancreatic cancer, CD11b + myeloid cells inhibit CD8 + Tcells by induction of PD-L1 in tumor cells in an epidermal growth factor receptor (EGFR)/mitogen-activated protein kinases-dependent manner.…”
Section: Tam Functions In Tumor Microenvironmentmentioning
confidence: 99%